Pragmatic Philanthropy - Shapiro, Ruth A.; Mirchandani, Manisha; Jang, Heesu (Springer Nature, 2021)
Asian Philanthropy and Charitable Organizations; Social Investment in Asia; Social Delivery Organizations; Relationships and Philanthropy in Asia; Ultra-high Net-worth Individuals in Asia; How Social Investment Works in Asia; Impact of Charitable Giving in Asia; Relationship with Elites and Social Investment in Asia